2004
DOI: 10.1038/sj.cgt.7700756
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal vector mediated delivery of the 3p FUS1 gene demonstrates potent antitumor activity against human lung cancer in vivo

Abstract: Lung cancer is one of the leading causes of death in the world. The underlying cause for lung cancer has been attributed to various factors that include alteration and mutation in the tumor suppressor genes. Restoration of normal function of the tumor suppressor gene is a potential therapeutic strategy. Recent studies have identified a group of candidate tumor suppressor genes on human chromosome 3p21.3 that are frequently deleted in human lung and breast cancers. Among the various genes identified in the 3p21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 18 publications
2
93
0
Order By: Relevance
“…On the basis of these findings re-introduction of FUS1 has entered phase I/II clinical trials for lung cancer using a nonviral nanoparticle-based systemic gene therapy. Using this method FUS1 does inhibit lung tumour xenograft growth in mice, reduces metastases and prolongs survival, however, this nanoparticle-based systemic therapy is problematic at present due to inflammatory responses Ito et al, 2004). Myristoylation was found to be essential for FUS1-mediated tumour suppression in vitro and in vivo (Uno et al, 2004).…”
Section: Fus1/tusc2mentioning
confidence: 99%
“…On the basis of these findings re-introduction of FUS1 has entered phase I/II clinical trials for lung cancer using a nonviral nanoparticle-based systemic gene therapy. Using this method FUS1 does inhibit lung tumour xenograft growth in mice, reduces metastases and prolongs survival, however, this nanoparticle-based systemic therapy is problematic at present due to inflammatory responses Ito et al, 2004). Myristoylation was found to be essential for FUS1-mediated tumour suppression in vitro and in vivo (Uno et al, 2004).…”
Section: Fus1/tusc2mentioning
confidence: 99%
“…96th Annual American Association for Cancer Research, April 2005). Of note, both the A549 and H1299 NSCLC cell lines are known have the 3p21.3 deletion and are deficient in the Fus1 protein (Kondo et al, 2001;Ito et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 We have previously demonstrated that the forced expression of wild-type (wt)-FUS1 significantly inhibited tumor cell growth by induction of apoptosis and alteration of cellcycle kinetics in 3p21.3-deficient NSCLC cells in vitro, and efficiently suppressed tumor growth and metastasis in mouse models of human lung cancer. 15,16 Molecular therapy by introduction of the TSGs, such as p53, into tumors has shown the potential to restore sensitivities to chemotherapy in primary lung cancers that lack p53 function. [17][18][19][20][21][22][23] However, no information has been available about the combined effects of exogenous expression of FUS1 tumor suppressor with any of various chemotherapeutic drugs on tumor suppression activity.…”
Section: Introductionmentioning
confidence: 99%